Hydrolysis-resistant and high-temperature-resistant polyamide composite material and preparation method thereof

By blending PA6 and PA66 and adding specific auxiliary materials, a hydrolysis-resistant and high-temperature-resistant polyamide composite material was prepared, which solved the problem that polyamide materials were difficult to meet the hydrolysis-resistant and high-temperature-resistant properties at the same time, and achieved widespread application in the field of high precision.

CN119529526AInactive Publication Date: 2025-02-28青岛瑞益信新材料科技有限公司
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411862822.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyamide materials are difficult to meet both hydrolysis and high temperature resistance, especially in applications such as electronics and aerospace.

Method used

By blending PA6 and PA66, and adding toughening agents, compatibility agents, lubricants, antioxidants and specific hydrolytic resistant agents, such as copper complex anti-hydrolytic agent SH3360 and sterically hindered aromatic carbodiimide anti-hydrolytic stabilizer AW700, boron nitride microspheres and aluminum borate whiskers loaded with ultrafine bamboo charcoal, a hydrolysis-resistant and high temperature-resistant polyamide composite material is prepared.

Benefits of technology

While maintaining the high temperature resistance of polyamide composite materials, this method significantly improves its hydrolysis resistance and is suitable for applications in high-precision fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193598690000101
    Figure BDA0005193598690000101
  • Figure BDA0005193598690000111
    Figure BDA0005193598690000111
  • Figure BDA0005193598690000121
    Figure BDA0005193598690000121
Patent Text Reader

Abstract

The invention relates to the field of advanced petrochemical and chemical new materials, and particularly discloses a hydrolysis-resistant and high-temperature-resistant polyamide composite material and a preparation method thereof. The polyamide composite material comprises the following raw materials in parts by weight: 5-7 parts of PA6 with the viscosity of 2.8-3.2; 80 to 83 parts of PA66, wherein the viscosity of the PA66 is 2.8 to 3.2; 8-12 parts of a toughening agent; 2-4 parts of a compatilizer; 0.5 to 1.5 parts of a lubricant; 0.3 to 0.9 part of an antioxidant; the hydrolysis-resistant agent is prepared from a copper complex hydrolysis-resistant agent SH3360 and a steric hindrance aromatic carbodiimide hydrolysis-resistant stabilizer AW700, and the weight ratio of the copper complex hydrolysis-resistant agent SH3360 to the steric hindrance aromatic carbodiimide hydrolysis-resistant stabilizer AW700 is 1: 1. The preparation method comprises the following steps: preparing raw materials; performing mixing; and extruding and granulating. The polyamide composite material disclosed by the invention has relatively excellent high temperature resistance and hydrolysis resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of advanced petrochemical new materials, and more specifically, to a hydrolysis-resistant and high-temperature-resistant polyamide composite material and a preparation method thereof. Background Art

[0002] Polyamide, commonly known as nylon, is a general term for thermoplastic resins containing repeated amide groups — [NHCO] — on the main chain of the molecule, including aliphatic PA, aliphatic-aromatic PA and aromatic PA. Polyamide composites are high-performance materials made by adding composite materials with polyamide as the matrix resin. They have excellent properties such as high strength, high stiffness, low density, corrosion resistance, and heat resistance, and are widely used in aerospace, automobile transportation, electronics, medicine and other fields.

[0003] PA66 and PA6 are the varieties with the largest output in the PA family. They have low production costs and can meet the needs of common usage scenarios, but they have the disadvantage of poor hydrolysis resistance. In the application of electronic devices such as mobile phone frames and smart watch shells, in order to improve fluidity and reduce deformation caused by water absorption, long carbon chain nylon products such as PA612 are usually used. PA612 not only has most of the general properties of general PA, such as lubricity, wear resistance, compression resistance and easy processing, but also has the characteristics of good toughness and softness, low water absorption, good dimensional stability, good salt resistance and hydrolysis resistance, and low density. However, compared with PA66, the mechanical properties of PA612 are significantly reduced, and the melting point is also reduced a lot. For example, the melting point of PA612 is 218℃, which is significantly lower than the melting point of PA66 at 262℃, which makes the high temperature resistance of PA612 significantly reduced compared with PA66. The longer the carbon chain, the lower the water absorption and the better the dimensional stability, but at the same time, the lower the strength and melting point, and the worse the high temperature resistance. Therefore, it is difficult to simultaneously meet the hydrolysis resistance and high temperature resistance of polyamide.

[0004] In order to maintain good hydrolysis resistance and high temperature resistance at the same time and make polyamide materials better suitable for high-precision fields such as electronics, aerospace, automobiles, and military industry, a new composite material needs to be designed. Summary of the invention

[0005] In order to improve both hydrolysis resistance and high temperature resistance, the present application provides a hydrolysis-resistant and high temperature-resistant polyamide composite material and a preparation method thereof.

[0006] In a first aspect, the present application provides a hydrolysis-resistant and high-temperature-resistant polyamide composite material, which adopts the following technical solution:

[0007] A hydrolysis-resistant and high-temperature-resistant polyamide composite material, comprising the following raw materials in parts by weight:

[0008] PA6 5-7 parts, viscosity 2.8-3.2;

[0009] PA66 80-83 parts, viscosity 2.8-3.2;

[0010] 8-12 parts of toughening agent;

[0011] 2 to 4 parts of compatibilizer;

[0012] 0.5-1.5 parts of lubricant;

[0013] 0.3-0.9 parts of antioxidant;

[0014] 0.5 to 1.5 parts of anti-hydrolysis agent, which includes copper complex anti-hydrolysis agent SH3360 and hindered aromatic carbodiimide anti-hydrolysis stabilizer AW700 in a weight ratio of 1:1.

[0015] By adopting the above technical solution, after PA66 and PA6 are blended, with the addition of auxiliary materials such as toughening agent, compatibilizer, lubricant and antioxidant, excellent high temperature resistance can be maintained. Since the hydrolysis process of nylon is a process in which the CN bond in the amide group is broken in the presence of water to form a carboxyl end group and an amino end group, the nylon molecular chain contains a highly polar amide group. During aging, water or organic matter containing -OH can easily penetrate into the nylon molecular chain to undergo hydrolysis and alcoholysis reactions, resulting in the rupture of the nylon molecular chain and damage to the mechanical properties. After the hydrolysis-resistant agent prepared by compounding the copper complex anti-hydrolysis agent SH3360 and the hindered aromatic carbodiimide anti-hydrolysis stabilizer AW700 is used, the hydrolysis-resistant agent will preferentially react with -OH and water molecules, reducing the contact between -OH and water molecules and the nylon molecular chain, thereby reducing and prolonging the hydrolysis of the amide bond in the nylon molecular chain, and can improve the hydrolysis resistance while maintaining good high temperature resistance. Therefore, the effect of simultaneously improving the hydrolysis resistance and high temperature resistance is obtained.

[0016] Optionally, the toughening agent is one or more of maleic anhydride grafted POE, ethylene terpolymer and EPDM-g-MAH, EPDM-g-MAH being more preferred.

[0017] Optionally, the compatibilizer is one or more of POE-g-GMA and EBA grafted GMA, and EBA grafted GMA is more preferred.

[0018] Optionally, the antioxidant is one or more of hindered phenol antioxidants, inorganic phosphate heat stabilizers, inorganic copper salt heat stabilizers, organic copper salt heat stabilizers, aromatic amine heat stabilizers, and SEED heat stabilizers. The combination of inorganic copper salt heat stabilizers and organic copper salt heat stabilizers has a better effect.

[0019] Optionally, the lubricant is one or more of PETS, SEBS, A560, polyethylene wax and oxidized paraffin. Polyethylene wax and oxidized paraffin have better compounding effect.

[0020] Optionally, the polyamide composite material further comprises boron nitride microspheres loaded with ultrafine bamboo charcoal and aluminum borate whiskers, wherein the weight portion of the boron nitride microspheres loaded with ultrafine bamboo charcoal is 3 to 9 parts, and the weight portion of the aluminum borate whiskers is 2 to 5 parts.

[0021] By adopting the above technical scheme, ultrafine bamboo charcoal can effectively promote the crystallization of PA6 / PA66, improve the structural strength of the composite material, and reduce the destructive ability of high temperature and water on the molecular chain. Boron nitride microspheres have excellent high temperature resistance and chemical stability, and can effectively improve the high temperature resistance of the composite material. Ultrafine bamboo charcoal can increase the roughness and active sites of the surface of boron nitride microspheres, thereby improving its interaction with the polyamide matrix and improving compatibility. Aluminum borate whiskers are insoluble in water and have good hydrolysis resistance. They can serve as a physical barrier to reduce the penetration of water into the composite matrix, thereby reducing the hydrolysis rate. Aluminum borate whiskers also have a certain stabilizer effect and can react with hydrolysis products to further improve the hydrolysis resistance of the composite material. Aluminum borate whiskers have a high aspect ratio and can form a three-dimensional network structure inside the composite matrix, which helps to improve the uniform distribution of ultrafine bamboo charcoal and boron nitride microspheres in the composite matrix, and can also provide steric hindrance, reduce the agglomeration of ultrafine bamboo charcoal and boron nitride microspheres, and improve their dispersibility. Therefore, the high temperature resistance and hydrolysis resistance of the polyamide composite material are improved at the same time.

[0022] Optionally, the preparation method of the boron nitride microspheres loaded with ultrafine bamboo charcoal is:

[0023] Dispersion of ultrafine bamboo charcoal: adding ultrafine bamboo charcoal powder into anhydrous ethanol and performing ultrasonic dispersion to evenly disperse the ultrafine bamboo charcoal to form a stable ultrafine bamboo charcoal dispersion;

[0024] Surface modification of boron nitride microspheres: Take silane coupling agent KH550, dissolve it in anhydrous ethanol, prepare a 1wt% solution, add boron nitride microspheres to the silane coupling agent solution, the amount of boron nitride microspheres used is twice that of ultrafine bamboo charcoal, stir to make the silane coupling agent evenly cover the surface of the boron nitride microspheres, filter, wash and dry;

[0025] Loading: Add the surface-modified boron nitride microspheres into the ultrafine bamboo charcoal dispersion, stir to make the ultrafine bamboo charcoal evenly distributed on the surface of the boron nitride microspheres, filter, wash and dry to obtain the boron nitride microspheres loaded with ultrafine bamboo charcoal, with the particle size controlled to be 10 μm.

[0026] Optionally, the polyamide composite material further comprises modified montmorillonite, the weight portion of the modified montmorillonite is 4 to 6 parts, and the particle size of the modified montmorillonite is 400 to 600 nm;

[0027] The preparation method of the modified montmorillonite comprises the following steps: adding natural montmorillonite to anhydrous ethanol, performing ultrasonic dispersion, making the natural montmorillonite uniformly dispersed in the anhydrous ethanol, and forming a montmorillonite suspension; dissolving a silane coupling agent in the anhydrous ethanol to prepare a 1wt% silane coupling agent solution, wherein the silane coupling agent adopts KH550, and the weight ratio of the silane coupling agent to the natural montmorillonite is 2:5; adding the montmorillonite suspension to the silane coupling agent solution, and then adding polytetrafluoroethylene nanoparticles, wherein the weight ratio of the polytetrafluoroethylene nanoparticles to the natural montmorillonite is 1:5, and stirring evenly, so that the silane coupling agent and the polytetrafluoroethylene nanoparticles fully react and adhere to the surface of the natural montmorillonite; washing, filtering, and drying until constant weight is reached, thereby obtaining the modified montmorillonite.

[0028] By adopting the above technical scheme, montmorillonite has a high specific surface area, can form an intercalation structure, improve the impact resistance and toughness of polyamide composite materials, and can also improve the thermal stability of polyamide composite materials. After montmorillonite is modified by silane coupling agent and polytetrafluoroethylene nanoparticles, it is helpful to improve its compatibility in the polyamide composite matrix, and improve the hydrophobicity of the montmorillonite surface, thereby improving the hydrolysis resistance of the polyamide composite material. After montmorillonite is modified by silane coupling agent, the high temperature resistance of modified montmorillonite is reduced. By adding polytetrafluoroethylene nanoparticles, this defect is effectively made up, the high temperature resistance of modified montmorillonite is improved, and the high temperature resistance of polyamide composite materials is further improved. Modified montmorillonite can be filled in the three-dimensional network structure formed by aluminum borate whiskers, fill the gaps, and form gradations of different specifications with boron nitride microspheres loaded with ultra-fine bamboo charcoal, thereby improving the compactness of each structure of the composite material, and further reducing the damage of water and high temperature to the composite material.

[0029] In a second aspect, the present application provides a method for preparing a hydrolysis-resistant and high-temperature-resistant polyamide composite material, which adopts the following technical solution:

[0030] A method for preparing a hydrolysis-resistant and high-temperature-resistant polyamide composite material comprises the following steps:

[0031] Raw material preparation: dry PA6 and PA66, and prepare the raw materials according to the ratio;

[0032] Mixing: Mix and stir all the raw materials to make them evenly dispersed;

[0033] Extrusion granulation: Use a twin-screw extruder for melt blending, the heating temperature of the front zone of the extruder is 275-285°C, and the heating temperature of the rear zone is 235-255°C; the extruded material is cooled and cut into granules, and then dried to obtain a polyamide composite material.

[0034] By adopting the above technical solution, the prepared polyamide composite material has excellent hydrolysis resistance and high temperature resistance.

[0035] In summary, this application has the following beneficial effects:

[0036] 1. Since the present application adopts the copper complex anti-hydrolysis agent SH3360 and the hindered aromatic carbodiimide anti-hydrolysis stabilizer AW700, the anti-hydrolysis agent will preferentially react with -OH and water molecules, reducing the contact between -OH and water molecules and nylon molecular chains, thereby reducing and prolonging the hydrolysis of amide bonds in the nylon molecular chains, and can improve the hydrolysis resistance of polyamide composite materials while maintaining good high temperature resistance.

[0037] 2. Boron nitride microspheres and aluminum borate whiskers loaded with ultrafine bamboo charcoal are preferably used in this application, because ultrafine bamboo charcoal can effectively promote the crystallization of PA6 / PA66, improve the structural strength of the composite material, and reduce the destructive ability of high temperature and water to the molecular chain. Boron nitride microspheres have excellent high temperature resistance and chemical stability, which can effectively improve the high temperature resistance of the composite material. Aluminum borate whiskers are insoluble in water and have good hydrolysis resistance. They can be used as a physical barrier to reduce the penetration of water into the composite matrix, thereby reducing the hydrolysis rate. Aluminum borate whiskers also have a certain stabilizer effect and can react with the hydrolysis product to further improve the hydrolysis resistance of the composite material. The three are compounded and can interact with each other, reduce agglomeration, and promote compatibility and dispersibility. Therefore, the effect of improving the high temperature resistance and hydrolysis resistance of the polyamide composite material is obtained.

[0038] 3. The polyamide composite material prepared by the method of the present application has excellent high temperature resistance and hydrolysis resistance. DETAILED DESCRIPTION

[0039] The present application is further described in detail with reference to the following examples. It is specially noted that if no specific conditions are specified in the following examples, the conventional conditions or the conditions recommended by the manufacturer are followed, and the raw materials used in the following examples can be obtained from common commercial sources unless otherwise specified.

[0040] PA6, brand is BASF of Germany.

[0041] PA66, brand is BASF of Germany.

[0042] Toughening agent:

[0043] Maleic anhydride grafted POE, brand DuPont MN493D; ethylene terpolymer, Elvaloy PTW, brand DuPont; EPDM-g-MAH, brand VA1801, brand ExxonMobil.

[0044] Compatibilizer:

[0045] POE-g-GMA, brand: Jiayirong, model: SOG-03; EBA grafted GMA, brand: DuPont Elvaloy PTW.

[0046] Antioxidants:

[0047] New high-efficiency hindered phenol antioxidant 1098; inorganic phosphate heat stabilizer, powder, H10; inorganic copper salt heat stabilizer H320 / H321; organic copper salt heat stabilizer H3337 / H3376; aromatic amine heat stabilizer H1802; SEED heat stabilizer. All are commercially available.

[0048] Hydrolysis resistant agent:

[0049] SH3360 copper complex anti-hydrolysis agent was purchased from Dongguan Sanhe Chemical Co., Ltd.; AW700 hindered aromatic carbodiimide anti-hydrolysis stabilizer was purchased from Shanghai Laian Industrial Co., Ltd.

[0050] Lubricant:

[0051] PETS, brand Lonza, USA, model GLYCOLUBEP; SEBS, brand Kraton, USA, grade MD8703; A560, ethylene acrylic acid copolymer, commonly used as a toughening agent, premium grade, purchased from Guangzhou Huiwangcheng Chemical Co., Ltd.; polyethylene wax, brand Xingyuan Chemical, model H-110; oxidized paraffin, industrial grade, brand Huijinchuan.

[0052] Ultrafine bamboo charcoal, 12000 mesh, was purchased from Zhejiang Wanglin Biotechnology Co., Ltd.

[0053] Boron nitride microspheres, micron grade, CAS No. 1344-2-2, brand Chaotai.

[0054] Aluminum borate whisker, CAS No. 61279-70-7, premium grade, brand Lana White.

[0055] Natural montmorillonite, nanometer grade, brand Naite.

[0056] Polytetrafluoroethylene nanoparticles, brand 3M, USA, grade TF-9207.

[0057] Example

[0058] Example 1

[0059] A hydrolysis-resistant and high-temperature-resistant polyamide composite material comprises the following raw materials:

[0060] PA6 5kg, viscosity 2.8; PA66 83kg, viscosity 2.8; toughener 8kg, toughener is EPDM-g-MAH; compatibilizer 2kg, compatibilizer is EBA grafted GMA; lubricant 0.5kg, lubricant is polyethylene wax and oxidized paraffin in a weight ratio of 2:3; antioxidant 0.3kg, antioxidant is inorganic copper salt heat stabilizer and organic copper salt heat stabilizer in a weight ratio of 2:1; hydrolysis resistance agent 0.5kg, hydrolysis resistance agent includes copper complex anti-hydrolysis agent SH3360 and hindered aromatic carbodiimide anti-hydrolysis stabilizer AW700 in a weight ratio of 1:1.

[0061] A method for preparing a hydrolysis-resistant and high-temperature-resistant polyamide composite material comprises the following steps:

[0062] Raw material preparation: Dry PA6 and PA66 by continuous air blowing at 80°C for 4 hours to remove moisture, and prepare the raw materials according to the ratio.

[0063] Mixing: Mix all raw materials at a stirring temperature of 110°C, a stirring speed of 60 rpm, and a mixing time of 15 min to ensure that all raw materials are evenly dispersed.

[0064] Extrusion granulation: Use a twin-screw extruder for melt blending, the heating temperature of the front zone of the extruder is 275°C, the heating temperature of the rear zone is 235°C, the screw aspect ratio is 44:1, the screw diameter is 60mm, and the screw speed is 400rpm; the extruded material is cooled and cut into pellets with a diameter of 5mm and a length of 8mm, and then dried to obtain a polyamide composite material.

[0065] Example 2

[0066] The difference between this embodiment and embodiment 1 is that the amount and specification of each raw material are different, see Table 1 for details.

[0067] A method for preparing a hydrolysis-resistant and high-temperature-resistant polyamide composite material comprises the following steps:

[0068] Raw material preparation: same as Example 1.

[0069] Mixing: Same as Example 1.

[0070] Extrusion granulation: Use a twin-screw extruder for melt blending, the heating temperature of the front zone of the extruder is 280°C, the heating temperature of the rear zone is 245°C, the screw aspect ratio is 44:1, the screw diameter is 60mm, and the screw speed is 400rpm; the extruded material is cooled and cut into pellets with a diameter of 5mm and a length of 8mm, and then dried to obtain a polyamide composite material.

[0071] Example 3

[0072] The difference between this embodiment and embodiment 1 is that the amount and specification of each raw material are different, see Table 1 for details.

[0073] A method for preparing a hydrolysis-resistant and high-temperature-resistant polyamide composite material comprises the following steps:

[0074] Raw material preparation: same as Example 1.

[0075] Mixing: Same as Example 1.

[0076] Extrusion granulation: Use a twin-screw extruder for melt blending, the heating temperature of the front zone of the extruder is 285°C, the heating temperature of the rear zone is 255°C, the screw aspect ratio is 44:1, the screw diameter is 60mm, and the screw speed is 400rpm; the extruded material is cooled and cut into pellets with a diameter of 5mm and a length of 8mm, and then dried to obtain a polyamide composite material.

[0077] Example 4

[0078] The difference between this embodiment and embodiment 2 is that the toughening agent is an ethylene terpolymer.

[0079] Example 5

[0080] The difference between this embodiment and embodiment 2 is that the toughening agent is maleic anhydride grafted POE.

[0081] Example 6

[0082] The difference between this embodiment and embodiment 2 is that POE-g-GMA is used as the compatibilizer.

[0083] Example 7

[0084] The difference between this embodiment and embodiment 2 is that PETS is used as the lubricant.

[0085] Example 8

[0086] The difference between this embodiment and embodiment 2 is that SEBS is used as lubricant.

[0087] Example 9

[0088] The difference between this embodiment and embodiment 2 is that the lubricant used is A560.

[0089] Example 10

[0090] The difference between this embodiment and embodiment 2 is that the antioxidant is a hindered phenol antioxidant.

[0091] Embodiment 11

[0092] The difference between this embodiment and embodiment 2 is that the antioxidant is an inorganic phosphate heat stabilizer.

[0093] Example 12

[0094] The difference between this embodiment and embodiment 2 is that the antioxidant adopts an aromatic amine heat stabilizer.

[0095] Embodiment 13

[0096] The difference between this embodiment and embodiment 2 is that the antioxidant adopts SEED heat stabilizer.

[0097] Table 1 Amount and specifications of raw materials in Examples 1-13

[0098]

[0099]

[0100]

[0101] Embodiment 14

[0102] The difference between this embodiment and embodiment 2 is that the polyamide composite material further comprises boron nitride microspheres loaded with ultrafine bamboo charcoal and aluminum borate whiskers, the amount of boron nitride microspheres loaded with ultrafine bamboo charcoal is 3 kg, and the amount of aluminum borate whiskers is 2 kg.

[0103] The preparation method of boron nitride microspheres loaded with ultrafine bamboo charcoal is as follows:

[0104] Dispersion of ultrafine bamboo charcoal: Add 2 kg of ultrafine bamboo charcoal powder into 40 L of anhydrous ethanol and perform ultrasonic dispersion for 1 hour at a power of 200 W to evenly disperse the ultrafine bamboo charcoal to form a stable ultrafine bamboo charcoal dispersion.

[0105] Surface modification of boron nitride microspheres: Take 0.4 kg of silane coupling agent KH550, dissolve it in 40 L of anhydrous ethanol, prepare a 1 wt% solution, take 4 kg of boron nitride microspheres and add them to the silane coupling agent solution, stir for 3 hours at a stirring speed of 500 rpm to make the silane coupling agent evenly cover the surface of the boron nitride microspheres, filter the boron nitride microspheres, wash with anhydrous ethanol to remove the unreacted silane coupling agent, repeat filtering and washing three times until the unreacted silane coupling agent is completely removed, and vacuum dry the washed boron nitride microspheres at 50 ° C until constant weight.

[0106] Loading: Add the surface-modified boron nitride microspheres into the ultrafine bamboo charcoal dispersion and stir for 3 hours to make the ultrafine bamboo charcoal evenly distributed on the surface of the boron nitride microspheres. Filter the loaded boron nitride microspheres and then wash them with anhydrous ethanol to remove the unattached ultrafine bamboo charcoal. Repeat the filtration and washing for 3 times and vacuum dry them at 50°C until constant weight. To obtain boron nitride microspheres loaded with ultrafine bamboo charcoal, the particle size is controlled to be 10 μm.

[0107] Embodiment 15

[0108] The difference between this embodiment and embodiment 14 is that the amounts of boron nitride microspheres and aluminum borate whiskers loaded with ultrafine bamboo charcoal are different, see Table 2 for details.

[0109] Example 16

[0110] The difference between this embodiment and embodiment 14 is that the amounts of boron nitride microspheres and aluminum borate whiskers loaded with ultrafine bamboo charcoal are different, see Table 2 for details.

[0111] Embodiment 17

[0112] The difference between this embodiment and embodiment 15 is that in this embodiment, the ultrafine bamboo charcoal is not loaded on the boron nitride microspheres, but is added to the raw materials and mixed separately, the amount of the ultrafine bamboo charcoal is 2 kg, and the amount of the boron nitride microspheres is 4 kg.

[0113] Embodiment 18

[0114] The difference between this embodiment and embodiment 17 is that no ultrafine bamboo charcoal is added in this embodiment.

[0115] Embodiment 19

[0116] The difference between this embodiment and embodiment 17 is that boron nitride microspheres are not added in this embodiment.

[0117] Embodiment 20

[0118] The difference between this embodiment and embodiment 15 is that aluminum borate whiskers are not added in this embodiment.

[0119] Embodiment 21

[0120] The difference between this embodiment and embodiment 17 is that in this embodiment, ultrafine bamboo charcoal and aluminum borate whiskers are not added.

[0121] Embodiment 22

[0122] The difference between this embodiment and embodiment 17 is that boron nitride microspheres and aluminum borate whiskers are not added in this embodiment.

[0123] Embodiment 23

[0124] The difference between this embodiment and embodiment 15 is that in this embodiment, boron nitride microspheres loaded with ultrafine bamboo charcoal are not added.

[0125] Embodiment 24

[0126] The difference between this embodiment and embodiment 15 is that the polyamide composite material further includes modified montmorillonite, the amount of the modified montmorillonite is 4 kg, and the particle size of the modified montmorillonite is 400 nm.

[0127] The preparation method of modified montmorillonite is:

[0128] Take 5kg of natural montmorillonite and add it into 200L of anhydrous ethanol. Perform ultrasonic dispersion for 1h at a power of 200W to evenly disperse the natural montmorillonite in the anhydrous ethanol to form a montmorillonite suspension.

[0129] 2 kg of silane coupling agent was dissolved in 2 L of anhydrous ethanol to prepare a 1 wt % silane coupling agent solution. The silane coupling agent used was KH550.

[0130] The montmorillonite suspension was added to the silane coupling agent solution, and then 1 kg of polytetrafluoroethylene nanoparticles were added, and stirred at a speed of 500 rpm for 3 hours until the mixture was uniformly stirred, so that the silane coupling agent and the polytetrafluoroethylene nanoparticles fully reacted and adhered to the surface of the natural montmorillonite.

[0131] The modified montmorillonite was filtered out and washed with anhydrous ethanol, and the washing and filtering were repeated for 3 times until the filtrate was neutral. The washed modified montmorillonite was vacuum dried at 50°C for 4 hours until constant weight was obtained, and the modified montmorillonite was obtained, and the particle size was controlled to be 400nm.

[0132] Embodiment 25

[0133] The difference between this embodiment and embodiment 24 is that the amount and particle size of the modified montmorillonite are different, see Table 2 for details.

[0134] Embodiment 26

[0135] The difference between this embodiment and embodiment 24 is that the amount and particle size of the modified montmorillonite are different, see Table 2 for details.

[0136] Embodiment 27

[0137] The difference between this embodiment and embodiment 25 is that no polytetrafluoroethylene nanoparticles are added during the preparation of the modified montmorillonite in this embodiment.

[0138] Embodiment 28

[0139] The difference between this embodiment and Embodiment 25 is that natural montmorillonite is used instead of modified montmorillonite in this embodiment.

[0140] Table 2 Amounts and specifications of raw materials in Examples 14-28

[0141]

[0142]

[0143]

[0144] Comparative Example

[0145] Comparative Example 1

[0146] The difference between this comparative example and Example 2 is that no anti-hydrolysis agent is added.

[0147] Comparative Example 2

[0148] The difference between this comparative example and comparative example 1 is that PA612 is used to replace PA6 and PA66.

[0149] Comparative Example 3

[0150] The difference between this comparative example and Example 2 is that the anti-hydrolysis agent is all copper complex anti-hydrolysis agent SH3360.

[0151] Comparative Example 4

[0152] The difference between this comparative example and Example 2 is that the anti-hydrolysis agent is all hindered aromatic carbodiimide anti-hydrolysis stabilizer AW700.

[0153] Table 3 Amount and specification of each raw material in comparative examples 1-4

[0154]

[0155]

[0156] Performance testing

[0157] Detection method / test method

[0158] 1. Heat deformation temperature: with reference to "GB / T 1634.2-2019 Determination of deformation temperature of plastics under load Part 2: Plastics and hard rubber", the polyamide composite materials prepared in each embodiment and comparative example were tested using method A with a bending stress of 1.8 MPa. The test results of the deformation temperature under load are detailed in Table 4.

[0159] 2. Water absorption: Referring to "GB / T 1034-2008 Determination of water absorption of plastics", the sample thickness is 2.05 mm ± 0.5 mm, and method 1 is used to test the water absorption after immersion in 23°C water for 24 hours. The polyamide composite materials prepared in each embodiment and comparative example are tested, and the water absorption mass fractions measured under different methods are shown in Table 4.

[0160] 3. Tensile strength: referring to "GB / T 1040.2-2022 Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", type 1A specimen was used, and the polyamide composite materials prepared in each embodiment and comparative example were tested under the test conditions of room temperature, after heat aging and after wet heat aging.

[0161] The tensile strength test of the samples at room temperature was carried out directly. The test results are shown in Table 4.

[0162] The test requirements after thermal aging are as follows: place the sample in an aging test box, set the temperature to 150°C, and after aging for 0h, 1000h and 3000h, place the aged sample in a 23°C dry environment to cool for 12h, and test the tensile strength after aging. The tensile strength test results are detailed in Table 4.

[0163] The test requirements after wet heat aging are as follows: place the sample in a closed pressure vessel filled with G12 antifreeze, raise the temperature to 135°C, take out the sample after aging for 0h, 500h and 1000h, rinse the solution on the surface of the sample after aging with distilled water, place it at 23°C, 50% RH to cool for 12h, and test the tensile strength after aging. The test results are detailed in Table 4.

[0164] Table 4 Test results of various embodiments and comparative examples

[0165]

[0166]

[0167] Combining Example 2 with Comparative Example 1, Comparative Example 2 and Table 4, it can be seen that the polyamide composite material of the present application, which adopts PA6 / PA66 with various auxiliary materials, especially with the addition of a hydrolysis-resistant agent, has excellent hydrolysis resistance and high temperature resistance.

[0168] Combining Example 2 and Comparative Examples 1 to 4 and Table 4, it can be seen that when the copper complex anti-hydrolysis agent SH3360 and the hindered aromatic carbodiimide anti-hydrolysis stabilizer AW700 are used in combination, the effect is optimal.

[0169] Combining Example 2 with Examples 4 to 13 and Table 4, it can be seen that different auxiliary materials have different performance improvement effects, and the formula and ratio of Example 2 have the best effect.

[0170] Combining Example 2 and Example 15 with Table 4, it can be seen that when the boron nitride microspheres loaded with ultrafine bamboo charcoal and the aluminum borate whiskers are added to the polyamide composite material, the hydrolysis resistance and high temperature resistance are significantly improved. In particular, combining Example 2, Example 15 and Examples 17 to 23 with Table 4, it can be seen that when the boron nitride microspheres loaded with ultrafine bamboo charcoal and the aluminum borate whiskers are compounded, the effect is best improved.

[0171] Combining Example 15 and Example 25 with Table 4, it can be seen that when modified montmorillonite is added to the polyamide composite material, the high temperature and hydrolysis resistance is improved again. In particular, combining Example 15, Example 25, Example 27, and Example 28 with Table 4, it can be seen that when modified montmorillonite modified with a silane coupling agent and polytetrafluoroethylene nanoparticles is used, the effect is best.

[0172] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A hydrolysis-resistant and high-temperature-resistant polyamide composite material, characterized in that: The invention comprises the following raw materials in parts by weight: PA6 5-7 parts, viscosity 2.8-3.2; PA66 80-83 parts, viscosity 2.8-3.2; 8-12 parts of toughening agent; 2 to 4 parts of compatibilizer; 0.5-1.5 parts of lubricant; 0.3-0.9 parts of antioxidant; 0.5 to 1.5 parts of anti-hydrolysis agent, which includes copper complex anti-hydrolysis agent SH3360 and hindered aromatic carbodiimide anti-hydrolysis stabilizer AW700 in a weight ratio of 1:

1.

2. The hydrolysis-resistant and high-temperature-resistant polyamide composite material according to claim 1, characterized in that: The toughening agent is one or more of maleic anhydride grafted POE, ethylene terpolymer and EPDM-g-MAH.

3. The hydrolysis-resistant and high-temperature-resistant polyamide composite material according to claim 1, characterized in that: The compatibilizer is one or more of POE-g-GMA and EBA grafted GMA.

4. The hydrolysis-resistant and high-temperature-resistant polyamide composite material according to claim 1, characterized in that: The antioxidant is one or more of a hindered phenol antioxidant, an inorganic phosphate heat stabilizer, an inorganic copper salt heat stabilizer, an organic copper salt heat stabilizer, an aromatic amine heat stabilizer, and a SEED heat stabilizer.

5. The hydrolysis-resistant and high-temperature-resistant polyamide composite material according to claim 1, characterized in that: The lubricant is one or more of PETS, SEBS, A560, polyethylene wax and oxidized paraffin.

6. The hydrolysis-resistant and high-temperature-resistant polyamide composite material according to claim 1, characterized in that: The polyamide composite material also includes boron nitride microspheres loaded with ultrafine bamboo charcoal and aluminum borate whiskers. The weight portion of the boron nitride microspheres loaded with ultrafine bamboo charcoal is 3 to 9 parts, and the weight portion of the aluminum borate whiskers is 2 to 5 parts.

7. The hydrolysis-resistant and high-temperature-resistant polyamide composite material according to claim 6, characterized in that: The preparation method of boron nitride microspheres loaded with ultrafine bamboo charcoal is as follows: Dispersion of ultrafine bamboo charcoal: adding ultrafine bamboo charcoal powder into anhydrous ethanol and performing ultrasonic dispersion to evenly disperse the ultrafine bamboo charcoal to form a stable ultrafine bamboo charcoal dispersion; Surface modification of boron nitride microspheres: Take silane coupling agent KH550, dissolve it in anhydrous ethanol, prepare a 1wt% solution, add boron nitride microspheres to the silane coupling agent solution, the amount of boron nitride microspheres used is twice that of ultrafine bamboo charcoal, stir to make the silane coupling agent evenly cover the surface of the boron nitride microspheres, filter, wash and dry; Loading: Add the surface-modified boron nitride microspheres into the ultrafine bamboo charcoal dispersion, stir to make the ultrafine bamboo charcoal evenly distributed on the surface of the boron nitride microspheres, filter, wash and dry to obtain the boron nitride microspheres loaded with ultrafine bamboo charcoal, with the particle size controlled to be 10 μm.

8. The hydrolysis-resistant and high-temperature-resistant polyamide composite material according to claim 6, characterized in that: The polyamide composite material also includes modified montmorillonite, the weight portion of the modified montmorillonite is 4 to 6 parts, and the particle size of the modified montmorillonite is 400 to 600 nm; The preparation method of the modified montmorillonite comprises the following steps: adding natural montmorillonite to anhydrous ethanol, performing ultrasonic dispersion, making the natural montmorillonite uniformly dispersed in the anhydrous ethanol, and forming a montmorillonite suspension; dissolving a silane coupling agent in the anhydrous ethanol to prepare a 1wt% silane coupling agent solution, wherein the silane coupling agent adopts KH550, and the weight ratio of the silane coupling agent to the natural montmorillonite is 2:5; adding the montmorillonite suspension to the silane coupling agent solution, and then adding polytetrafluoroethylene nanoparticles, wherein the weight ratio of the polytetrafluoroethylene nanoparticles to the natural montmorillonite is 1:5, and stirring evenly, so that the silane coupling agent and the polytetrafluoroethylene nanoparticles fully react and adhere to the surface of the natural montmorillonite; washing, filtering, and drying until constant weight is reached, thereby obtaining the modified montmorillonite.

9. The method for preparing a hydrolysis-resistant and high-temperature-resistant polyamide composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Raw material preparation: dry PA6 and PA66, and prepare the raw materials according to the ratio; Mixing: Mix and stir all the raw materials to make them evenly dispersed; Extrusion granulation: Use a twin-screw extruder for melt blending, the heating temperature of the front zone of the extruder is 275-285°C, and the heating temperature of the rear zone is 235-255°C; the extruded material is cooled and cut into granules, and then dried to obtain a polyamide composite material.

Citation Information

Patent Citations

  • Weather-resistant modified nylon 6 material for automobile plastic part

    CN103665840A

  • Whisker reinforced thermally conductive plastic material and preparation method thereof

    CN104559146A

  • Continuous glass-fiber reinforced polyamide composite material with thermo-oxidative aging resistance and hydrolysis resistance and preparation method thereof

    CN107778853A

  • PC / ABS alloy with high weather resistance, hydrolysis resistance and antistatic property, and preparation method thereof

    CN111004489A

  • Halogen-free flame-retardant nylon material and preparation method thereof

    CN112409785A